Urgent surgical department in multidisciplinary hospital repurposed as infectious hospital for new coronavirus infection (COVID-19) - A. Yu. Korolkov; V. M. Teplov; D. A. Zaitsev; E. A. Tcebrovskaya; T. O. Nikitina (Вестник хирургии имени И.И. Грекова)
Objective. In this paper, we show the work of the emergency surgical department on the example of a large repurposed multidisciplinary hospital, also its necessity even for infectious hospitals not accepting patients with acute surgical pathology.Methods and Materials. The work of surgical department of Pavlov First Saint Petersburg State Medical University repurposed for COVID-19 patients was analyzed. About 1500 COVID-19 patients were hospitalized during 4-month period.Results. All patients undergoing surgery were in severe condition (at intensive care unit). Most common surgery in abdomen was diagnostic laparoscopy. Spontaneous bleedings of different localization occurred in these patients, what required endovascular and endoscopic treatment. We observed only Clavien – Dindo 1-degree postoperative complications. Mortality rate was high and amounted to 75 %.Conclusion. The work of surgical department in an infectious hospital for the treatment of a new coronavirus infection is extremely difficult. An infectious hospital should have a 24-hour diagnostic service (US, CT, MRI). Patients severity and the working conditions necessitate the availability of the trained surgical personnel. Given the high risks of bleedings in patients with COVID-19, it is necessary to have a 24-hour endoscopy and endovascular surgery departments with the ability to perform diagnostic and therapeutic interventions.